ANALISIS KEPUASAN ATAS KUALITAS PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH (RSUD) KOTA SEMARANG - Ela Indriani; Endang Larasati; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Along with the increasing levels of education, science, medical technology and the rapid socio-economic conditions of the awareness of the importance of health in the community, resulting an improvements of the quality of health care, thus becoming a basic requirement, where health services are quality is expected by the public. One of the health service which is owned by the City of Semarang named Semarang Regional General Hospital. The purpose of this study was to determine the level of patient satisfaction with health care quality Semarang Regional General Hospital, then knowing how to improve satisfaction over the quality of health services in Semarang Regional General Hospital. The author using a technique quantitative data analysis using mean to find the average score the implementatiton level service performance and the average level of the interest of service. There are 23 indicators of quality of service that is used as material assesment of performance and the interests of the service. The average of service performance indicator is 2,72, so that an indicator that has the value of the average under the needs to be improved, while the average of interest indicator is 3,54 so that an indicator that has the value of the average above that the need attentionfor its performance. Based on the results of this study that there are still some indicators of quality of service which should be a priority in the repair, because it is still bad and comfort are important, that the waiting room or ward patients, completeness of medical equipment and patient care space, the ability of personnel to provide services in accordance with the procedures and information provided, courtesy and friendliness of clerk, the trust of patient to the hospital personel, risk-free and danger, fairness in providing services.